Assessing teacher training needs who teach students with learning difficulties integrated in Jordan - خزاعله احمد خالد; النصراوين معين سلمان (Latakia University Journal - Arts and Humanities Sciences Series, 2020)
The aim of this study was to evaluate the training needs of teachers who are teaching students with learning disabilities integrated in Amman Governorate schools. The study sample consisted of (300) teachers, the reasearcher used a quastioneer developed after reviwing the literature also its valdity and relability were assured. The study showed that there are medium training needs for teachers who are teaching students with learning disabilities integrated in Amman Governorate schools.